Bangladesh : The Experience and Perceptions of Public Officials - Mukherjee, Ranjana; Gokcekus, Omer; Manning, Nick; Landell-Mills, Pierre (Washington, DC: World Bank, 2013)
This report summarizes the responses of Bangladeshi Class I (highest level) public sector officials to a survey seeking opinions on a number of civil service issues, from personnel management practices to rewards and disciplinary actions, and from employees' sources of income to the budget environment and procurement processes. Survey results show instances in Bangladesh's civil service where professional conduct is perceived to be sacrificed at the expense of personal and political concerns. Surveyed officials express a concern over patronage appointments in the recruitment of Class III and IV staff and unfavorable postings and transfers at the higher level. Corruption, insufficient budgetary allocation, and unpredictable budgets are identified as key impediments to achieving organizational objectives. The report utilizes the survey data to test prior assertions against the survey data. Data is analyzed to establish that institutions do matter for accountability; to explore an empirical association between elements of institutional environment and accountability; and to generate potential accountability payoffs for certain reform interventions. The analyzes show that reduced interference by politicians from outside and within the organizations, less micro-management by very senior civil servants and merit-based recruitment to Class I jobs will be most effective in reducing the perception of pervasive corruption.